Current and projected characteristics and unique health care needs of the patient population served by the Department of Veterans Affairs (Rand Corporation, 2015)
The Veterans Access, Choice, and Accountability Act of 2014 addressed the need for access to timely, high-quality health care for veterans. Section 201 of the legislation called for an independent assessment of various aspects of veterans' health care. The RAND Corporation was tasked with an assessment of the current and projected demographics and health care needs of patients served by the Department of Veterans Affairs (VA). The number of U.S. veterans will continue to decline over the next decade, and the demographic mix and geographic locations of these veterans will change. While the number of veterans using VA health care has increased over time, demand will level off in the coming years. Veterans have more favorable economic circumstances than non-veterans, but they are also older and more likely to be diagnosed with many health conditions. Not all veterans are eligible for or use VA health care. Whether and to what extent an eligible veteran uses VA health care depends on a number of factors, including access to other sources of health care. Veterans who rely on VA health care are older and less healthy than veterans who do not, and the prevalence of costly conditions in this population is projected to increase. Potential changes to VA policy and the context for VA health care, including effects of the Affordable Care Act, could affect demand. Analysis of a range of data sources provided insight into how the veteran population is likely to change in the next decade.